Persepsi mahasiswa Program Studi Gizi Kesehatan terhadap citra tubuh ahli gizi - Agustina Arundina Triharja Tejoyuwono; Toto Sudargo; Retna Siwi Padmawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: As health professionals, nutritionists are supposed to have good body image, although nutritionists may be overweight or obese. Body image of nutritionists will determine the quality of nutrition service particularly in giving evidence and assurance to the clients. As nutritionist-to-be, nutrition students are expected to have good knowledge and appearance because these will reflect quality of nutritionists in the future.Objective: To identify perception of students of health nutrition study program of the Faculty of Medicine about body image of nutritionists.Method: The study used qualitative descriptive method and case study design. It was carried out in Yogyakarta from October to December 2008. Subject of the study were 23 undergraduate students of Health Nutrition Study Program of Gadjah Mada University of both class A and B. Data were obtained through focus group discussion and in-depth interview. Data validity and reliability used source and method triangulation to 7 lectures of health nutrition Gadjah Mada University.Results: Body image was someone’s physical appearance as viewed by one or others and the effect of mass media in the assessment of body image was relatively significant. Body image of nutritionists was important because it would affect trust of the clients and success in counseling. Nutritionists had responsibility in giving an exemplary healthy life to the community either in physical image or appearance so that nutritionists were supposed to have ideal body posture and good body performance.Conclusion: Good body image for nutritionists would determine quality of counseling and trust of the clients. Nutritionists had responsibility to give an exemplary healthy life to the community. Therefore it was necessary to do monitoring and socialization from the academics as well as related institutions such as association of nutritionists about body image of nutritionists and nutrition students from now on and in the future.